2017
DOI: 10.1016/j.plabm.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis of liver: Interference of serpins in quantification of SERPINA4 – A preliminary study

Abstract: BackgroundCirrhosis of liver is a pathological condition, wherein functions of liver are impaired by chronic liver exploitations. Due to decrease in synthetic capacity, expressions of plasma proteins tend to decrease in blood stream. Serpins (Serine protease inhibitors) are class of plasma proteins expressed from liver with structural similarities and diverse functions. SERPINA4 (Kallistatin) is a multifunctional serpin clade A protein expressed from liver and concentration in serum is the reflection of extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
(25 reference statements)
0
6
0
1
Order By: Relevance
“…Serpina4-ps1 is a pseudogene of the serine proteinase inhibitor superfamily that originates from clade A member 4 [ 43 ]. The functional gene Serpina4 , also known as kallistatin, is abundant in the liver and a potent vasodilatory protein involved in the prevention of cardiovascular disease [ 44 ]. Recently, a case–control study [ 45 ] demonstrated that Serpina4 was down-regulated in the liver of obese NAFLD patients and plays critical roles in the inhibition of inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Serpina4-ps1 is a pseudogene of the serine proteinase inhibitor superfamily that originates from clade A member 4 [ 43 ]. The functional gene Serpina4 , also known as kallistatin, is abundant in the liver and a potent vasodilatory protein involved in the prevention of cardiovascular disease [ 44 ]. Recently, a case–control study [ 45 ] demonstrated that Serpina4 was down-regulated in the liver of obese NAFLD patients and plays critical roles in the inhibition of inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Serpin family A member 4 (SERPINA4), also known as kallistatin, is a novel antiangiogenesis protein, which exerts various effects on inflammation, angiogenesis and tumor growth (61,62). Previous studies reported that SERPINA4 suppressed tumor growth by directly inhibiting cancer cell proliferation, migration and invasion, and by adjusting cancer cell signaling in various malignant tumors, including lung and breast cancers, and HCC (61–63). Kallistatin levels were positively correlated with free androgen index in women with polycystic ovary syndrome (64).…”
Section: Discussionmentioning
confidence: 99%
“…Primary antibodies (polyclonal and monospecific antibodies separately) were diluted (1:100) and PVDF membranes were incubated in diluted primary antibody solution at room temperature with slow shaking on rocker for 2 to 3 hours. PVDF membranes were washed with 1x PBST thrice for 3 minutes each [15,16].…”
Section: Western Blotmentioning
confidence: 99%